Multi-phase structured silicon carbon nitride thin films prepared by hot-wire chemical vapour deposition - Badaruddin, M.R.; Muhamad, M.R.; Rahman, S.A. (2011)
In this work, Silicon Carbon Nitride (Si-C-N) thin films were deposited by Hot Wire Chemical Vapour Deposition (HWCVD) technique from a gas mixture of silane (SiH4), methane (CH4) and nitrogen (N-2). Six sets of Si-C-N thin films were produced and studied. The component gas flow rate ratio (SiH4:CH4:N-2) was kept constant for all film samples. The total gas flow-rate (SiH4 + CH4 + N-2) was changed for each set of films resulting in different total gas pressure which represented the deposition pressure for each of these films ranging from 40 to 100 Pa. The effects of deposition pressure on the chemical bonding, elemental composition and optical properties of the Si-C-N were studied using Fourier transform infrared (FTIR) spectroscopy, Auger Electron Spectroscopy (AES) and optical transmission spectroscopy respectively. This work shows that the films are silicon rich and multi-phase in structure showing significant presence of hydrogenated amorphous silicon (a-Si:H) phase, amorphous silicon carbide (a-SiC), and amorphous silicon nitride (a-SiN) phases with Si-C being the most dominant. Below 85 Pa, carbon content is low, and the films are more a-Si:H like. At 85 Pa and above, the films become more Si-C like as carbon content is much higher and carbon incorporation influences the optical properties of the films. The properties clearly indicated that the films underwent a transition between two dominant phases and were dependent on pressure. (C) 2011 Elsevier B.V. All rights reserved.